REASONS OF DOMESTIC VIOLENCE - Urazaliev Murod Koraevich (International Journal of Business, Law and Political Science, 2025)
Objective: This article aims to explore the causes and negative aspects of domestic violence, emphasizing its psychological mechanisms and examining methods of prevention. It investigates the theories surrounding aggression and violence in human behavior. Method: The study utilizes psychological theories, including Sigmund Freud's concept of "aggression capacity," the "psychological theory of aggression," and contributions from the Yale University Research Group. It also analyzes the "aggression-frustration doctrine" and "coercive power," incorporating findings from recent studies to understand human violence. Result: The research highlights the multifaceted nature of human aggression, suggesting that physical violence is often used as a last resort when other methods to achieve a desired outcome fail. The study underscores the importance of understanding the causes of domestic violence and its connection to broader criminological theories. Novelty: This article contributes a comprehensive view on the psychological and criminological aspects of domestic violence, integrating both classic and contemporary theories. It calls for a deeper understanding of various biological and social factors, offering scientifically substantiated insights for addressing and reducing domestic violence.